Strategies of coping with failure in the structure of managers` professional burnout syndrome = Strategie radzenia sobie z porażką w strukturze syndromu wypalenia zawodowego menedżerów - Rongińska, Tatiana; Doliński, Artur (Zielona Góra: Faculty of Economics and Management Press)
The report presents the results of research on predictors of professional burnout syndrome among women and men working in management positions. The research included over 2000 people working in a variety of workplaces.
Keywords: professional burnout syndrome; resignation; coping with failure; offensive strategy; syndrom wypalenia zawodowego; rezygnacja; radzenie sobie z porażką; strategia ofensywna